2020
DOI: 10.1038/s41598-020-71205-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir in the treatment of hep C among patients on hemodialysis: a systematic review and meta-analysis

Abstract: Hepatitis C virus (HCV) infection among maintenance hemodialysis patients is implicated in increased morbidity and mortality compared to uninfected patients. Sofosbuvir (SOF)-based regimens may not be optimal among patients requiring hemodialysis. Several studies, however, provide evidence that use of SOF among HCV-positive patients with renal impairment, is effective and safe. We searched Pubmed and Embase to identify studies reporting the efficacy and safety of SOF-based regimens for the treatment of HCV-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…The pooled incidence of SAE due to SOF-based regimen in our study was 11%, which was similar to the study by Li T et al, in which the pooled SAE rate for DAA-based antiviral therapies in HCV/Stage 4-5 CKD patients was 12.1% [51]. Shehadeh et al also reported a 10% incidence for SAE, which is quite similar to our results [20].…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…The pooled incidence of SAE due to SOF-based regimen in our study was 11%, which was similar to the study by Li T et al, in which the pooled SAE rate for DAA-based antiviral therapies in HCV/Stage 4-5 CKD patients was 12.1% [51]. Shehadeh et al also reported a 10% incidence for SAE, which is quite similar to our results [20].…”
Section: Plos Onesupporting
confidence: 91%
“…In a recent systematic review, the safety and efficacy of Sofosbuvir was explored among patients on HD [20] and results are quite similar to the results of the current study. However, there is a very important difference between the two studies.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings were comparable to the previous some studies. [13,14] We found that hypertension was the most common comorbidity found in 15 (55.55%) patients followed by obesity 8 (29.63%) and diabetes found in 3 (14.81%). [15] Among 27 cases 20 (74.04%) were naïve and 7 (25.96%) were treatment experienced.…”
Section: Resultsmentioning
confidence: 94%
“…[15] Among 27 cases 20 (74.04%) were naïve and 7 (25.96%) were treatment experienced. [13,14] Sustained virological response was found in 26 (96.3%) and 1 (3.7%) patients were lost at follow up. In 15 patients who were treated with SOF of 200 mg vs. 400 mg alternate day, the figure in Bhamidimarri et al [16] was 91% vs75% SVR12.…”
Section: Resultsmentioning
confidence: 95%